Tunable Nanoscale Metal‒Molecule‒Semiconductor Junctions Via Light-Controlled Molecular Orientation - Ponce-Hormazabal, I (John Wiley and Sons Inc, 2025)
Molecular electronics offers significant potential for the development of miniaturized and tunable electronic devices, with silicon (Si) remaining a cornerstone of modern semiconductor technology. This study presents a method for constructing tunable molecular circuits on Si electrodes using UV-controlled hydrosilylation reaction, enabling precise control over molecular orientation and bonding. When hydrogen-terminated Si surfaces are exposed to UV light in a solution of 9-decyne-1-ol, hydroxyl (OH) groups form covalent Si─O─C bonds, while in the absence of UV light, alkyne groups instead react to form Si─C bonds. This tunability allows precise positioning of oxygen atoms near the Si surface, thereby enhancing charge transfer in metal–molecule–semiconductor junctions and at electrified semiconductor–electrolyte interfaces. Conducting atomic force microscopy (C-AFM) measurements reveal that Pt─Si junctions exhibit Schottky diode characteristics, whereas Pt–molecule–Si junctions display Ohmic behaviour. Junctions formed via Si─O bonds demonstrate significantly lower resistance and at least a two-fold higher electron transfer rate constant (ket) compared to those formed with Si─C bonds, indicating superior charge transfer when oxygen atoms are positioned near the Si electrode. These findings suggest that incorporating oxygen-containing molecules reduces the space-charge region, thereby facilitating current flow at the Si–metal and Si–electrolyte electrified interfaces. © 2025 The Author(s). Small published by Wiley-VCH GmbH.